The Magnetic Elastic Dispersion (ESP) - Páez, Jorge (1985)
We present a study of elastic scattering of an electron in constant homogeneous magnetic field. The dependency of the cross section on the electron spin orientation is given. If the spin polarization is along or against the external field, then the cross section is four times larger than the cross section if the spin polarization pointed along its own motion.